Analisis Penjualan Parfum Berbasis E-Commerce pada UMKM Demanda Parfum Surabaya - Zahra Embun Kusumaningtiyas; Nur Saidah Agustina; Rika Yuliastanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
In the world of commerce, or commonly known as e-commerce, leveraging the development of internet technology is a significant step that can be very beneficial. E-commerce not only simplifies the sales information system process from manual to computerized but also changes the relationships and interactions of ordering, payment, and viewing products, allowing users to check transaction history anytime and anywhere. For this reason, the author tries to utilize the knowledge gained during university studies to analyze and design e-commerce for the Demanda parfum. The authors conducted an analysis and design for this study. Demanda Parfum is a business that offers various brands and types of perfumes. Seruni Parfum has a broad business idea to introduce perfume brands both from domestic and international markets. Over time, the number of perfume enthusiasts has been increasing, and companies with perfume sales concepts prioritize the needs of every individual. The authors analyzed the sales system in place at Seruni Parfum, which currently operates with a web-based system. At the perfume factory, monthly reports are still manually created in many cases. The transaction data processing is also done manually, meaning there is a possibility of errors and mistakes during writing and calculations. Therefore, e-commerce is needed to support these tasks, allowing sales to be conducted efficiently and generating reports accurately.